2016
DOI: 10.1002/cbdv.201500262
|View full text |Cite
|
Sign up to set email alerts
|

New Cyclohexadepsipeptides from an Entomogenous Fungus Fusarium proliferatum and Their Cytotoxicity and Autophagy‐Inducing Activity

Abstract: Five new cyclohexadepsipeptides termed as enniatins R - V (1 - 5) and seven known cyclohexadepsipeptides (6 - 12) were isolated from the solid culture of Fusarium proliferatum, a fungus isolated from the cadaver of an unidentified insect collected in Tibet. Their structures were elucidated by NMR and MS spectroscopic analysis. The X-ray single-crystal structure of 6 was reported for the first time. Enniatins R and S represented the first enniatins incorporating with an unusual 2,3-dihydroxy-isovaleric acid (Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The above NMR data suggested that compound 4 possessed three N Me amino acid and three 2-hydroxycarboxylic acid units. Comparison of the NMR data of 4 with those reported suggested that 4 belonged to a group of enniatins . In addition, the molecular weight of 4 is 14 mass units higher than MK1688 ( 9 ), indicating one additional methyl group in 4 .…”
Section: Resultsmentioning
confidence: 61%
“…The above NMR data suggested that compound 4 possessed three N Me amino acid and three 2-hydroxycarboxylic acid units. Comparison of the NMR data of 4 with those reported suggested that 4 belonged to a group of enniatins . In addition, the molecular weight of 4 is 14 mass units higher than MK1688 ( 9 ), indicating one additional methyl group in 4 .…”
Section: Resultsmentioning
confidence: 61%
“…Beauvenniatin F ( 105 ) was isolated from an entomogenous fungus Fusarium proliferatum from the cadaver of an unidentified insect collected in Tibet, and exhibited strong cytotoxicity against K562/A (adriamycin-resistant K562) cells with IC 50 value of 3.78 μM, and autophagy-inducing activity at the concentration of 20 μM in GFP-LC3 stable HeLa cells [ 86 ]. Beauvenniatins F ( 105 ), G 1 ( 106 ), G 2 ( 107 ), G 3 ( 108 ), H 1 ( 109 ), H 2 ( 110 ), and H 3 ( 111 ) from the fungus Acremonium sp.…”
Section: Cyclic Hexadepsipeptidesmentioning
confidence: 99%
“…Beauvenniatin F has exhibited strong cytotoxicity against adriamycin-resistant myelogenous leukemia cells (K-562), with an IC 50 of 2.78 μM, and autophagy-inducing activity at a concentration of 20 μM in green fluorescent protein-light chain 3-stable HeLa cells [ 94 ]. These depsipeptides also displayed cytotoxicity against epithelial carcinoma (KB), lymphoma (BC), and lung carcinoma cells (NCI-H187), with IC 50 values ranging from 1.00 to 2.29 μM as well as against kidney epithelial cells (Vero) at 1.9–5.5 μM [ 95 ].…”
Section: Depsipeptides With a Recognized Mechanism Of Targeting Cance...mentioning
confidence: 99%